The Byronic hero : types and prototypes - Thorslev, Peter L. (University of Minnesota Press, 1962)
This study of the origins and development of the Romantic hero through its apogee in the works of Byron critically examines the major Romantic heroes of comparative literature and places them in the wider perspective of history.